The role of serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in the efficacy evaluation of patients with membranous nephropathy: Serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in membranous nephropathy - Zheng, Kaiyuan; Qu, Tongxin; Han, Lili; Sun, Yi (Journal of Medical Biochemistry, 2025)
Objective: Monocyte chemoattractant protein-1 (MCP-1), serum B-cell activating factor (BAFF), complement B factor (CFB), and anti-M-type phospholipase A2 receptor (PLA2R) antibodies are investigated in connection with membranous nephropathy (MN) and their roles in evaluating the efficacy of treatment. Methods: 108 patients who were hospitalized to our hospital between January 2023 and June 2024 were chosen to serve as research participants. Patients were divided into remission and nonremission groups according to their clinical efficacy. The levels of serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in patients with positive and negative anti-PLA2R and different pathological stages were compared, and the clinical data of the remission group and the nonremission group were compared. The association between serum levels of BAFF, CFB, and MCP-1 and anti-PLA2R antibody levels in patients who tested positive for anti-PLA2R antibody. The predictive efficacy of serum anti-PLA2R antibodies, BAFF, CFB, and MCP-1 for nonremission in MN patients after therapy was evaluated using receiver operating characteristic (ROC) curves. Results: There were 78 patients who were positive for anti-PLA2R antibodies and 30 patients who were negative for anti-PLA2R antibodies. The levels of serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in patients positive for anti-PLA2R antibodies were significantly greater than those in patients negative for anti-PLA2R antibodies (P<0.05). The comparison of the serum BAFF, CFB and MCP-1 levels in MN patients at different stages were as follows: stage I < stage II < stage III < stage IV. Serum BAFF, CFB, and MCP-1 in patients positive for anti-PLA2R antibodies were positively correlated with the level of anti-PLA2R antibodies (r=0.792, 0.823, 0.832, P<0.001). Spearman correlation analysis revealed that the levels of serum BAFF, CFB, and MCP-1 in MN patients were positively correlated with pathological stage (rs=0.758, 0.752, 0.717, P<0.001). The pathological stage and anti-PLA2R antibody, BAFF, CFB and MCP-1 levels in the nonremission group were significantly greater than those in the remission group (P<0.05). After treatment, elevated serum levels of MCP-1, CFB, and BAFF were risk factors for nonremission in MN patients (P<0.05). The ROC curve analysis revealed that the area under the curve for the combined prediction of nonremission in MN patients after treatment with serum BAFF, CFB and MCP-1 was 0.948, which was greater than the area under the curve for the individual prediction of anti-PLA2R antibody and BAFF, CFB and MCP-1 (Z=4.116, 3.059, 4.122, 4.116, P<0.05). Conclusion: The levels of serum BAFF, CFB and MCP-1 in MN patients are related to the level of anti-PLA2R antibody, MN stage and therapeutic effect. Moreover, the combined detection of serum BAFF, CFB and MCP-1 has high predictive value for the nonremission of MN patients after treatment.